Does expert judgement is important in mining industry?: A systematic literature review - Ismail, Siti Noraishah; Ramli, Azizan; Abdul Aziz, Hanida (Penerbit Universiti Malaysia Pahang, 2022)
The Delphi technique is used to achieve consensus from a panel of experts on particular issues by several series or rounds. Previous scholars widely used Delphi in social science studies, business, healthcare, education and many more. However, there is a lack of systematic review on the contribution of Delphi in the engineering and technology field of research. Thus, the aims of this systematic literature review (SLR) are to investigate the contribution of Delphi in solving problems for the past 11 years in the mining industry and to understand the future outlook of Delphi in the Malaysian mining industry. By applying the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), 37 selected papers were identified with three main themes and 24 subthemes created using thematic analysis. Based on the findings, the most highlighted contribution of Delphi came from Theme 3: Delphi’s derivatives (50.0%), followed by Theme 1: Mine lifecycle (12.5%), and Theme 2: Analysis of Delphi (37.5 %). In conclusion, an SLR could hopefully increase awareness among mining players to use Delphi in solving their problems which cannot be solved by machinery or tools in achieving a consensus among experts.